Ecclesiology and Missiology: Reflections on Two Recent Documents from the World Council of Churches. Issue 2 (June 2015) - Bevans, Stephen
Abstract In 2013 the World Council of Churches published two important documents, one on the church and one on mission. Beginning with the conviction that ecclesiology has to be missiological and missiology ecclesiological, this article reads each document from the basic perspective of the other. This reading is followed by a constructive critique from the author's perspective as a Roman Catholic missionary ecclesiologist.